2004
DOI: 10.3171/jns.2004.100.4.0688
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus-eluting stents in the canine cerebral vasculature: a prospective, randomized, blinded assessment of safety and vessel response

Abstract: No neurotoxic effects were observed in the intracranial vessel walls or brainstem tissue in which sirolimus-coated stents were implanted. Compared with bare-metal stents, the sirolimus-coated devices did not impair endothelialization and, furthermore, tended to reduce the proliferation of SMCs. These findings indicate that sirolimus-coated devices may inhibit in-stent stenosis. Further studies with longer-term follow up are required to assess the restenosis rates of sirolimus-coated stents implanted in the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…The safety of DES in the intracranial vasculature was studied in a model using Cypher (Cordis Corp) stents in the BA artery of dogs. 4 This study found no evidence of arterial or brain tissue toxicity and concluded that these devices were safe within the intracranial vasculature. The total dose of drug released to tissues by DES is very small compared with the known toxic doses of both sirolimus and paclitaxel, and tissue toxicity does not appear to be an issue.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The safety of DES in the intracranial vasculature was studied in a model using Cypher (Cordis Corp) stents in the BA artery of dogs. 4 This study found no evidence of arterial or brain tissue toxicity and concluded that these devices were safe within the intracranial vasculature. The total dose of drug released to tissues by DES is very small compared with the known toxic doses of both sirolimus and paclitaxel, and tissue toxicity does not appear to be an issue.…”
Section: Discussionmentioning
confidence: 70%
“…4 We have used DES to treat 8 patients with intractable cerebral ischemia attributable to intracranial atherosclerosis. In this report, we present our clinical results with angiographic follow-up.…”
mentioning
confidence: 99%
“…9,10 A study on the placement of sirolimus-eluting stents in canine cerebral arteries did not reveal histological evidence of toxicity. 11 This represents the largest experience to date with the use of DESs for these arteries. The compounds used on these stents, sirolimus and paclitaxel, have been shown to reduce the response of neointimal hyperplasia by blocking mitogen-induced smooth muscle proliferation.…”
Section: Discussionmentioning
confidence: 94%
“…This was the first published series describing the use of drug-eluting stents in humans after an initial study of sirolimus-coated Cypher stent (Cordis Corp.) deployment in canine basilar arteries showed promising results. 21 The group prospectively selected 8 patients with symptomatic intracranial stenosis that was greater than 70% and refractory to medical management. The authors used coronary drug-eluting stents to treat the patients' diseased vessels.…”
Section: Drug-eluting Stentsmentioning
confidence: 99%